The Role of Multi Purpose Cooperative in Developing Economic Independence or SMEâs - Thomas, Partono; Faruq, Muhammad Umar (JEJAK: Jurnal Ekonomi dan Kebijakan, 2017)
Cooperatives are seen as one of the important instrument to improve economic and social conditions of societies, to arouse the spirit of initiative and improving the general knowledge and technical skills of the society. On the present cooperatives members are business people of small medium scale enterprises (SMEs) which need a guidance or development. The purpose of this study is to describe the role of cooperatives in small medium scale enterprises (SMEs) development. The method used is descriptive qualitative. Data collection techniques used are observation, documentation and interview.The results of research showed that KSU Padurenan Jaya is a multi-purpose cooperatives that has five business units i.e. save loan, store, embroidery service, marketing, research and development. KSU Padurenan Jaya was instrumental in developing the small medium scale enterprises (SMEs) embroidery and convection consists of (1) aspects of the market, by following the events of the exhibition or expo, online marketing, providing material needs in the cooperative store, and create innovative products according to consumer taste. (2) the aspect of technology, by socialization and demonstration of the use technology of embroidery machines, embroidery design with computer programs, internet information technology for promoting and marketing product, And to optimize the use of the machine by provide services embroidery using advanced machine in cooperation so that can improve the productivity and efficiency of the business. (3) the aspect of the capital, by providing save loan service with simple procedures, mentoring to access other sources of financing.